PERANCANGAN WEBSITE SMKN 1 KOTA JAMBI MENGGUNAKAN PHP AND MYSQL - Sepriano Sepriano (Lembaga Pengembangan Kinerja Dosen, 2021)
Schools can use the website as a medium to share information with parents, teachers, and students more easily.The school communicates with other relevant agencies through the website as well.This study's objective isdeveloping an information system for SMKN 1 Kota Jambi school website.The waterfall model is used in the system approach method.Software development follows a methodical and sequential approach known as the waterfall model, beginning with the stages of analysis, design, code, testing, and maintenance.Because the Ministry of Education and Culture has synchronized the school's data through Dapodik data, the website design for SMKN 1 Kota Jambi requires a lot of new data to be entered before it can be displayed.